Petrography and geochemistry of Late Carboniferous dolostone-hosted soapstone in the Sherwan Formation, Hazara Basin: insights into hydrothermal and dynamic metamorphic processes - Khawaja Umair Majeed; Khawaja Umair Majeed; Muhammad Saleem Mughal; George Kontakiotis; Syed Kamran Ali; Shamim Akhtar; Hammad Tariq Janjuhah; Kamaran Siddique; Evangelia Besiou; Assimina Antonarakou (Frontiers in Earth Science)
IntroductionThis study investigates the petrography and geochemistry of soapstone-bearing dolomite within the Sherwan Formation, Hazara Basin, with a focus on understanding hydrothermal dynamic metamorphism and resolving the age controversy surrounding the host rock.MethodsField observations, petrographic analysis, and geochemical techniques were used, including X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive spectroscopy (EDS), to characterize mineral composition and alteration processes.ResultsPetrographic evidence confirms that talc formed through hydrothermal alteration of Late Carboniferous dolomite, facilitated by faulting, folding, and silica-rich fluid infiltration. Distinct geological features such as stromatolitic dolomite, pseudotachylitic veins, and mylonitization suggest episodic brittle deformation under high-temperature conditions. The presence of Anthracoporella spectabilis supports a Late Carboniferous age for the dolomite, while the soapstone is dated to the Permian, linked to Pre-Himalayan tectonics, Panjal volcanism, and dolerite intrusions. Mineralogical analyses reveal that soapstone is primarily composed of talc (steatite), with secondary minerals including brucite, magnesite, willemseite, and montmorillonite. The occurrence of pyrite and hematite indicates hydrothermal interactions, contributing to metal enrichment and oxidation.DiscussionGeochemical data show silica enrichment and structural weakening as key factors in dolomite-to-talc transformation. Trace levels of chromium (100–300 ppm) raise concerns over Cr6+ toxicity, but the absence of arsenic, lead, cadmium, and mercury supports the environmental safety and industrial potential of the soapstone. The study underscores the complex interplay of tectonic, metamorphic, and geochemical processes in the evolution of the Sherwan soapstone.